HOW DIET INFLUENCES CHILDREN'S ORAL HEALTH (REMUNOM, 2023)
Care with nutrition in early childhood is a unique factor when discussing oral health in childhood. Diet plays a fundamental role in children's oral health, when food is not taken care of, in addition to bad behavior in terms of oral hygiene, an oral environment is created that is conducive to the development of problems such as caries, dental malformation, eruption , receding gums, among other periodontal diseases and occlusion problems. This article aims to explore the relationship between diet and children's oral health, highlighting the main foods that contribute to the formation of caries, the role ofthe family in care and the performance of the dental professional. The choice of this theme is justified by the growing prevalence of oral diseases in children and the importance of an adequate diet for the prevention of these conditions. Understanding how diet influences children's oral health is crucial to promoting healthy eating habits since childhood, contributing to the reduction of oral problems and improving the quality of life of these individuals.